Survival of Listeria monocytogenes during in vitro gastrointestinal digestion after exposure to 5 and 0.5 % sodium chloride. (February 2019) - Pettersen, Kristin Sæbø; Skjerdal, Taran; Wasteson, Yngvild; Lindbäck, Toril; Vegarud, Gerd; Comi, Irene; Aspholm, Marina
Abstract: The food industry is under pressure to reduce the NaCl content in food, but the consequences on the ability of L. monocytogenes to survive in the human host and cause listeriosis is not known. In this study, a recently developed internationally harmonized static in vitro digestion (IVD) model was used to investigate the survival of L. monocytogenes in the gastric and intestinal phases after exposure to 5 or 0.5% NaCl. Six isolates from three Scandinavian foodborne listeriosis outbreaks, all related to NaCl containing foods, the EGDe reference strain and an EGDe mutant, deleted for the major stress regulator gene, sigB, were included. A ten-fold reduction of NaCl in the cultivation media significantly reduced the survival fraction of the EGDe strain in the IVD model while one of the clinical outbreak isolates showed a significantly increased survival fraction. Finally, the EGDe strain was able to attach and invade cultured HT-29 cells after passage through the IVD model. Altogether, these results suggest that a reduction of the NaCl content from 5 to 0.5% prior to exposure to the IVD model has the potential to cause a change in the relative survival fraction and that the effect is strain dependent. Highlights: A NaCl reduction in the culture media altered survival of L. monocytogenes strains in an in vitro digestion (IVD) model. The EGDe Δ sigB mutant demonstrated a reduced survival fraction in the IVD model compared to its EGDe background strain. The EGDe strain successfully invaded HT-29 cells after passage through the IVD model.